Pengaruh Beauty Influencer, Persepsi Harga dan Brand Image terhadap keputusan pembelian Hand and Body Lotion Vaseline di DIY - Carneli, Refika Dewi; Nurwahyudi, Muhammad Robi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This study aims to determine the influence of beauty influencers, price perceptions and brand image on purchasing decisions for Vaseline hand and body lotion (consumer case study in DIY). This study is a quantitative study, with data processing using SPSS version 25. The population in this study were consumers of Vaseline hand and body lotion aged 20-29 years, women and men in DIY. This study has a sample size of 100 people from the calculation results using the Solvin formula. Sample collection with simple random sampling where samples are taken randomly from the population. The findings in this study indicate that beauty influencers have a positive and significant effect on purchasing decisions, while price perceptions have a positive and significant effect on purchasing decisions and brand image has a positive and significant effect on purchasing decisions. While carried out simultaneously with beauty influencers, price perceptions and brand image have a positive and significant effect on purchasing decisions togethe.